Isolation, selection and active determination of bacteria produce uricase - Ha, Pham Thanh; Man, Tran Dinh; Hoa, Tran Thi (Academia Journal of Biology, 2013)
Uricase producing bacteria was isolated from soil with a nutrient agar media containing uric acid. The isolation of bacteria was based on uricolytic activity on agar surface. A bacterial strain CN3 showed a maximum zone of clearance in short time had been chosen. Based on morphological and biochemical tests, as well as 16S rRNA sequence and phylogenetic tree analysis, the bacterial isolated was identified as Pseudomonas putida. The uricase was present as intracellular and extracellular enzyme in this strain. When the strain was cultured at 30°C and pH7 for 48h on nutrient broth media containing uric acid 0.5%, the extracellular uricase activity peaked at 0.85 U/ml and intracellular uricase activity peaked at 0.45 U/ml.